EXPLORATION OF THE APPLICATION OF STORY-BASED SCIENCE LITERACY LEARNING STRATEGIES AND EXPERIMENTAL PROJECTS IN EARLY CHILDHOOD - Qibtiyatul Quro; Choiriyah Choiriyah (Journal of Early Childhood Education (JECE), 2021)
The purpose of writing this article is to explore learning strategies through playing science activities for early childhood during the Covid 19 pandemic. Research subjects on two students and teachers in PAUD RA. Al-Mannaan who applies learning strategies to improve early childhood scientific literacy. The results show that the exploratory learning strategy applied consists of two learning strategies through storytelling with pictures and an experimental project. The series of learning strategies are structured based on four aspects, namely: access, interaction, response, and results. During distance learning, children feel unburdened with schoolwork, children feel confident through activities that involve themselves, curiosity arises in children, and independence in making decisions. This article also explores the impact of teachers in such an environment, where teachers feel the importance of inculcating science literacy for early childhood so that children do not find science boring. The investigations carried out in this study also provide an overall indication based on the criteria set by the teacher that the application of the two learning strategies is effective in helping to strengthen scientific literacy in the PAUD RA. AL-Mannaan.